Pengaruh Pendidikan Kewirausahaan, Efikasi Diri Berwirausaha dan Faktor Lingkungan terhadap Minat Berwirausaha Mahasiswa Perguruan Tinggi Islam di Jember - Sri Wahyu Lelly Hana Setyanti; Erila Cahyani Pradana; Sudarsih Sudarsih (Jurnal Manajemen dan Kewirausahaan, 2021)
The study aims to know and test the influence of entrepreneurship education, entreprenuerial self efficacy and environmental factors to entrepreneurship interest of Islamic university students in Jember namely UNMUH and IAIN Jember. This research is explanatory research, with sample selection using quota sampling counted 40 samples in each research object with total sample 80. Then method used purposive sampling and data collection using accidental sampling. Analyzer used is multiple linear regression analysis. The results  indicate that entrepreneurship education, self-efficacy entrepreneurship and environmental factors have an effect on entrepreneurship interest.